2020
DOI: 10.3389/fnbeh.2020.584052
|View full text |Cite
|
Sign up to set email alerts
|

Mild Physical Activity Does Not Improve Spatial Learning in a Virtual Environment

Abstract: It is well-established that physical exercise in humans improves cognitive functions, such as executive functions, pattern separation, and working memory. It is yet unknown, however, whether spatial learning, long known to be affected by exercise in rodents, is also affected in humans. In order to address this question, we recruited 20 healthy young male adults (18–30 years old) divided into exercise and control groups ( n = 10 in each group). The exercise group performed three sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The radial arm maze task was first used to assess the spatial abilities of rodents by Olton and Samuelson [48] in 1976. Since then, the task has been adapted for use with humans in real [46,47,59] and virtual [4,34] settings. The basic version of the task consists of a central room, from which a certain number (usually 8) uniform corridors spread.…”
Section: Radial Armmentioning
confidence: 99%
“…The radial arm maze task was first used to assess the spatial abilities of rodents by Olton and Samuelson [48] in 1976. Since then, the task has been adapted for use with humans in real [46,47,59] and virtual [4,34] settings. The basic version of the task consists of a central room, from which a certain number (usually 8) uniform corridors spread.…”
Section: Radial Armmentioning
confidence: 99%
“…An effect of regular physical activity on spatial learning is supported by previous cross-sectional observations that higher cardiorespiratory fitness was positively linked with mnemonic precision in 2D 45 and 3D spatial memory task contexts 44 , 53 . On the other hand, a recent longitudinal study 79 involving 20 young adults found no direct evidence for improved spatial learning after a 12 weeks mild-intensity aerobic exercise intervention: The intervention neither affected relVO 2max , nor spatial learning in virtual maze tasks. This negative behavioral outcome, in comparison to our study, might be related to the shorter length and lower intensity of the exercise intervention 79 .…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, a recent longitudinal study 79 involving 20 young adults found no direct evidence for improved spatial learning after a 12 weeks mild-intensity aerobic exercise intervention: The intervention neither affected relVO 2max , nor spatial learning in virtual maze tasks. This negative behavioral outcome, in comparison to our study, might be related to the shorter length and lower intensity of the exercise intervention 79 .…”
Section: Discussionmentioning
confidence: 86%
“…These authors hypothesized that the low levels of regular PA in their sample were not sufficient to yield fitness-related improvements in object mnemonic discrimination, and, notably, the young adults in their study already showed superior high-interference memory performance than the older adults. Indeed, there may be an optimal level of cardiorespiratory fitness required to elicit exercise-related gains in hippocampal memory (Ben-Zeev et al., 2020; Pontifex et al., 2014) and pattern separation specifically (Bullock et al., 2018; Kovacevic et al., 2020), perhaps especially for healthy young adults who already have high baseline cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, larger (versus smaller) amounts of higher-intensity PA have been associated with more robust neurobiological changes (Voss et al, 2019) and greater cardiorespiratory fitness (Garber et al, 2011) that, in turn, may be critically important for exercise-induced benefits on hippocampal memory and pattern separation (Ben-Zeev et al, 2020;D ery et al, 2013;Heisz et al, 2017;Kovacevic et al, 2020;Pontifex et al, 2014;Voss et al, 2019). Thus, the purpose of the current study was to examine the influence of self-reported strenuous exercise habits on spatial pattern separation in a sample of young adult men and women, using a spatial memory task that was designed to putatively measure pattern separation for spatial locations across varying degrees of similarity (Williams et al, 2019).…”
Section: Introductionmentioning
confidence: 99%